Clinicopathological analysis of borderline ovarian tumours and risk factors related to recurrence: experience of single institution. (17th February 2019) - Sozen, Hamdullah; Vatansever, Dogan; Topuz, Samet; Iyibozkurt, Cem; Kandemir, Hulya; Yalçin, Ibrahim; Onder, Semen; Yavuz, Ekrem; Salihoglu, Yavuz
Abstract: This study was conducted to determine the demographic and clinicopathologic characteristics and evaluate the prognostic value of various factors, such as the extensiveness of surgery, related to the tumour itself and the clinical features in the recurrence of borderline ovarian tumours (BOT). We retrospectively evaluated the data of 103 patients with a borderline ovarian tumours treated at our institution between the years 2000 and 2012. The median age was 37 (16–79) years and the majority of the patients were premenopausal (76.7%). During the follow-up, 16 recurrences were observed (15.5%). The multivariate analysis showed that the micropapillary architecture and fertility sparing surgery were the only significant independent predictors for the development of a recurrence amongst all of the demographic and clinicopathological features. In our study group, we identified that the micropapillary architecture itself and the fertility sparing surgery had a significant impact on the development of a BOT recurrence. The patients who possess these features should be followed up more closely for a long time period. Impact statement: What is already known on this subject? A borderline ovarian tumour is known as a recurrent disease. The recurrence rate varies between 5 and 20%. It is well known in the literature that patients treated by an oophorectomy have a relatively lower risk of development of a recurrence compared to the patients treated by cystectomy. What do the results of this study add? Although some of the clinicopathological features are shown to be risk factors for the development of a recurrence in many studies, some of the pathological-clinical and the demographic features have not been described as yet, or have been considered to be equivocal regarding the development of a recurrence. In this study, we investigate all possible demographic, pathological, and clinical factors associated with a recurrence. Not only the well-known pathological characteristics but also the new pathological parameters and clinical approaches have been investigated. For instance, microinvasion architecture and lymphadenectomy speculated in the literature as the risk factors for the development of a recurrence, have not been identified as risk factors in our study. On the other hand, our statistical analyses have revealed that micropapillary architecture should be described as a risk factor for the development of a recurrence. What are the implications of these findings for clinical practice and/or further research? We hope our study becomes influential in the literature on the field of a micropapillary architecture and the development of a recurrence. The patients carrying this feature have to be followed up very closely and carefully. Furthermore, our findings have indicated no significant relation between the performing of a lymphadenectomy and the rate of a recurrence. This result might be encouraging for the gynaecological surgeons to refrain from a lymphadenectomy for the borderline ovarian tumours.